Determination of Some Trace Elements in Hair Dye Samples Available in Libyan Markets by Induction Plasma Emission Spectroscopy - Hanin Salah Abdalla Milad; Khalifa A. Alfallous; Abdelsalam Ali Asweisi (Postgraduate School Universitas Brawijaya, 2022)
The research aims to determine the concentrations of trace elements in some hair dyes imported and locally manufactured in Libyan markets. Collected 23 samples of henna and hair dyes from 11 brands, 6 brands of chemical hair dyes consisting of 3 colors, 1 brand of hair bleach, and 4 brands of henna dyes; we applied the standard digestion method, weighed 1g of each sample of hair dye and 0.5g of each model of henna, then mixed the piece with high purity nitric acid 69.5% and concentrated hydroxide acid 30% and put it on a hot plate until getting digested and after that were filtration them and Samples were dilute with deionized water. The concentration of iron, lead, cobalt, cadmium, chromium, tin, magnesium, potassium, and arsenic was measured using inductively coupled plasma optical emission spectrometry (ICP-OES). The results showed concentration of the trace elements in the samples ranged <0.001 to 0.07 ppm from chromium, 0.35 to 95.9 ppm from potassium.09 to 71.4 ppm from magnesium, 0.05 to 62.2 ppm from iron, 0.15 to 1.28 ppm from stannium. While the concentrations of the remaining elements of lead, cadmium, arsenic, and cobalt, the results were less than the detection limit. As for the physical analyses found that some values exceeded the standard limit. Keywords: hair dye, trace elements, icp-oes